Seed unit at ILCA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
ILCA (the International Livestock Centre for Africa) now has a Seed Unit, thanks to a grant from the Swiss Development Cooperabon Agency. The Unit will link ILCA's forage agronomy section (genetic resources FLAG and networks) and national seed...